Cognitive styles and clinical correlates of childhood abuse in bipolar disorder. (26th May 2014) - Perich, Tania; Mitchell, Philip B; Loo, Colleen; Hadzi‐Pavlovic, Dusan; Roberts, Gloria; Green, Melissa; Frankland, Andrew; Lau, Phoebe; Corry, Justine
<x xml:space="preserve">Abstract</x> Objectives In a relatively small number of previous studies, childhood abuse has been found to be associated with more severe symptom course, earlier onset, greater comorbidity, and greater suicidality in those diagnosed with bipolar disorder. There have been no prior reports looking for any association between childhood abuse and cognitive style. This study aimed to examine the relationship between cognitive factors, such as response styles to depressed mood and dysfunctional attitudes, clinical features, and childhood physical and sexual abuse in this population. Methods A total of 157 adult participants diagnosed with DSM‐IV bipolar disorder I or II were assessed on clinical features of this condition and measures of childhood sexual and physical abuse. Participants also completed self‐report questionnaires covering areas such as symptom measures of depression, anxiety and stress, dysfunctional attitudes, and response styles to depressed mood. Results Seventy‐four participants (37%) reported having experienced either sexual or physical abuse. Those who reported physical or sexual abuse were significantly more likely to report self‐harm or suicidal behaviors and showed higher stress scores. Specifically, those who reported sexual abuse were more likely to have simple phobias, to have attempted suicide, and to have had more hospitalizations for depression. After controlling for current mood severity, there were no significant differences on the self‐report cognitive style measures for those who reported childhood sexual or physical abuse compared to those who did not report abuse. Conclusions Cognitive styles were not found to be associated with childhood sexual or physical abuse in participants with bipolar disorder. Stress may be important to target in psychological interventions, whilst special attention should also be paid to those with a history of sexual abuse given the greater likelihood of suicide attempt.